Correlation of modal frequency variation for a bridge with operational and environmental actions - ZHOU Yi; SUN Li-min; XIE Mo-wen; QIAO Lan (工程科学学报)
In the vibration based structural health monitoring (VBSHM) field, the modal frequency of a structure is commonly used as an indicator for the global health condition of the structure. However, field measurements have shown that the modal frequency of a bridge varies with structural anomalies and the operational and environmental actions, e. g., temperature and traffic loading. Moreover, the latter variation usually exceeds the frequency shifts induced by the small and medium structural anomalies. To highlight the anomaly-induced frequency changes, the variability of modal frequencies of bridges with the operational and environmental actions must be investigated, and then, the action-induced frequency variations need to be eliminated. According to the periodic characteristics of the six-year monitoring data of the Donghai Bridge, this research identified the main actions that affected the modal frequencies of the first vertical/lateral bending modes and torsional mode of the girder of this bridge, and further, it compared the relative contributions of actions to the variability of frequencies through the partial correlation coefficients and the proposed cyclic averaging method. The results show that the modal frequencies of the Donghai Bridge vary at cycles as 1 a, 1 week, 1 d, and 12.42 h, which coincide with the inherent predominant cycles of structural temperature, traffic loading, wind loading, and sea levels, respectively. Structural temperature and traffic loading are the most influential factors for the frequency variation, and their relative importance is different for each individual cycle. The results also show that the cyclic averaging method can effectively separate the components in periods of 1 a, 1 week, and 1 d and can disclose the inherent correlation between actions and modal frequencies. This study helps in enhancing the understanding of the frequency variability for operational bridges and may lead to a more reliable evaluation of structural performance.